Analisis Nilai Moral Dalam Cerita Rakyat Sendang Sani Pati - Fara Fatika Maharani; Putri Jenar Mahesa Ayu; Nur Kusuma Astuti; Mohammad Kanzunnudin (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
The aim of this research is to analyze the moral values ​​contained in the Sendang Sani story. This study used qualitative research methods. Regarding the data source, it comes from a book entitled "East Coast folklore" written by Mohammad Kanzunnudin, published by CV Adhigama in 2024, page 230 and measuring 15.5 × 23 cm. The data is in the form of fragments of the Sendang Sani story. Data collection techniques using the reading and listening method. The data analysis technique uses Miles and Huberman's theory, namely (1) data collection, (2) data reduction, (3) data presentation, (4) drawing conclusions..